Human cytomegalovirus (HCMV) trends in Sri Lanka: insights from a hospital-based seroprevalence analysis - Narapity Pathirannehalage Sunil-Chandra; Madawala Vithanage Madusha Lakmali Jayasundara; Maththe Gama Ralalage Shobha Sanjeewani Gunathilaka; Suduwa Dewage Himal Suminda (BMC Infectious Diseases, 2025)
Abstract Background Human Cytomegalovirus (HCMV) spreads through direct contact with blood, and other body fluids such as urine, saliva and breast milk. It is transmitted sexually and can also be passed from a pregnant mother to fetus via the placenta. While often asymptomatic in healthy individuals, HCMV causes symptomatic infections in immunocompromised people and congenital infections in fetuses. It is a common global congenital infection and can lead to morbidity and occasional mortality in newborns. Latent HCMV may reactivate in immunosuppressed individuals. This study aimed to determine the age and gender specific seroprevalence of HCMV in selected populations in Sri Lanka. Methods A total of 820 blood samples obtained from 820 participants of selected low and high-risk populations in Sri Lanka, namely; hospital inpatients (n = 200), antenatal women (n = 80), blood donors (n = 80), cancer patients (n = 200), Sexually Transmitted Disease (STD) clinic attendees (n = 160) and Chronic Kidney Disease (CKD) patients on haemodialysis (n = 100) were tested for IgG antibodies against HCMV by Enzyme Linked Immunosorbent Assay (ELISA). Statistical analysis was performed using IBM SPSS Statistics version 30 (IBM® Corporation, New York, USA). Results Overall HCMV seroprevalence was found to be 94.9% (778/820), whereas in males it was 95.2% (395/415) and in females it was 94.6% (383/405) (p = 0.691). Seroprevalence of HCMV in hospital inpatients, antenatal women, blood donors, cancer patients, STD clinic attendees and CKD patients on haemodialysis were found to be 92.5% (185/200), 100% (80/80), 90% (72/80), 96% (192/200), 93.1% (149/160) and 100% (100/100) respectively. Overall seroprevalence of HCMV increases with age ranging from 94.3% (33/35) in 15–19 years age group to 98.8% (84/85) in ≥ 60 years age group. Conclusions Seroprevalence of HCMV in diverse low and high-risk populations of Sri Lanka was studied for the first time. HCMV seroprevalence is similar between genders (p > 0.05) and increases with age. Over 90% of individuals are infected with HCMV by age 15, indicating a high prevalence of primary infections from early childhood to adolescence. This study provides essential background information on HCMV infection and its impacts in diverse populations of Sri Lanka and aids in executing preventive and therapeutic measures in high-risk populations.